Determination of Pharmaceutical Residues by UPLC-MS/MS Method: Validation and Application on Surface Water and Hospital Wastewater - Bui Van Hoi; Cam-Tu Vu; Lan-Anh Phung-Thi; Thao Thi Nguyen; Phuong Thanh Nguyen; Huong Mai; Phuong-Thu Le; Thanh-Hien Nguyen; Dao Thanh Duong; Hue Nguyen Thi; Dung Le-Van; Dinh Binh Chu (Journal of Analytical Methods in Chemistry)
In this study, an analytical method for the simultaneous determination of 7 major pharmaceutical residues in Vietnam, namely, carbamazepine, ciprofloxacin, ofloxacin, ketoprofen, paracetamol, sulfamethoxazole, and trimethoprim, in surface water and hospital wastewater has been developed. The method includes enrichment and clean-up steps by solid phase extraction using mix-mode cation exchange, followed by identification and quantification using an ultrahigh-performance liquid chromatography and tandem mass spectrometry and employing electrospray ionization (UPLC-ESI-MS/MS). Seven target compounds were separated on the reversed phase column and detected in multiple reaction monitoring (MRM) mode within 6 minutes. The present study also optimized the operating parameters of the mass spectrometer to achieve the highest analytical signals for all target compounds. All characteristic parameters of the analytical method were investigated, including linearity range, limit of detection, limit of quantification, precision, and accuracy. The important parameter in UPLC-ESI-MS/MS, matrix effect, was assessed and implemented via preextraction and postextraction spiking experiments. The overall recoveries of all target compounds were in the ranges from 55% to 109% and 56 % to 115% for surface water and hospital wastewater, respectively. Detection limits for surface water and hospital wastewater were 0.005–0.015 µg L−1 and 0.014–0.123 µg L−1, respectively. The sensitivity of the developed method was allowed for determination of target compounds at trace level in environmental water samples. The in-house validation of the developed method was performed by spiking experiment in both the surface water and hospital wastewater matrix. The method was then applied to analyze several surface water and hospital wastewater samples taken from West Lake and some hospitals in Vietnam, where the level of these pharmaceutical product residues was still missed. Sulfamethoxazole was present at a high detection frequency in both surface water (33% of analyzed samples) and hospital wastewater (81% of analyzed samples) samples.